Multifocal Stevens-Johnson syndrome after concurrent phenytoin and cranial and thoracic radiation treatment, a case report. - Kandil, Abdullah O.; Dvorak, Tomas.; Mignano, John.; Wu, Julian K.; Zhu, Jay-Jiguang. (2016)
Abstract: A 46 year old male patient with metastatic prostate cancer developed Stevens-Johnson syndrome (SJS), initially in three well-demarcated areas on his scalp, chest and back, corresponding to ports of radiation therapy while on phenytoin. The rash spread from these locations and became more generalized and associated with pain and sloughing in the mucous lining of the mouth. There is a documented association between phenytoin administration with concurrent cranial radiation therapy and development of SJS. Erythema multiforme (EM) associated with phenytoin and cranial radiation therapy (EMPACT) is the term that describes this reaction. However, this term may not cover the full spectrum of the disease since it describes EM associated with phenytoin and only cranial radiation therapy. This case report presents evidence that SJS may be induced by radiation to other parts of the body in addition to the cranium while phenytoin is administered concomitantly. With increasing evidence that phenytoin and levetiracetam are equally efficacious for seizure treatment and prophylaxis, and since there is no link identified so far of an association between levetiracetam and SJS, we believe that levetiracetam is a better option for patients who need anticonvulsant medication(s) while undergoing radiation therapy, especially cranial irradiation.; Keywords: Anti-Epileptic Drugs, Stevens-Johnson Syndrome, Erythema Multiforme associated with Phenytoin And Cranial Radiation Therapy, Erythema Multiforme, Toxic Epidermal Necrolysis.; Springer Open.